The Roles of School-Based Law Enforcement Officers and How These Roles Are Established: A Qualitative Study. (June 2016) - McKenna, Joseph M.; Martinez-Prather, Kathy; Bowman, Scott W.
Recently, considerable attention has been directed to violence and misbehavior in U.S. schools. In turn, schools have looked for solutions to address such concerns, one of which is the use of law enforcement officers. The aim of this research is to explore how law enforcement officers define their actual roles, as well as their perceived roles in an educational setting. Also, this study examines the process for establishing these roles within the school environment. A total of 26 law enforcement officers were contacted by phone and participated in an in-depth interview. Each interview was transcribed into NVivo, and subsequently coded to identify general themes and common phrases. The findings suggest that officers working in the school environment are taking on many roles, some of which they do not consider appropriate. In addition, who establishes these roles varies considerably. The findings are discussed in terms of their deviation from prior literature as well as needed future research endeavors.